A Graphene Oxide‐based Covalent Resorufin‐Conjugated Fluorescence "OFF‐ON" Probe for Detection of Hydrazine. Issue 12 (5th May 2022) - Guo, Qiang; Zhang, Jie; Sun, Hongyan; Chen, Jian Lin
Abstract: The unique properties of graphene oxide (GO), such as good water solubility, non‐toxicity, biocompatibility and cell permeability, make GO well suited for a number of biological applications. In this study, we explore the application of GO as an efficient fluorescent quencher for a highly fluorescent organic dye, resorufin (RF). The quenching effect of GO on resorufin is studied by noncovalent and covalent bonding of resorufin, respectively. The fluorescence is completely quenched when resorufin is covalently linked to GO; while resorufin's fluorescence could be still observed through noncovalent bonding to GO sheet. Interestingly, addition of hydrazine into RF‐GO complex causes the fluorescence recovered, providing a potential ''OFF‐ON'' fluorescence responsive probe for detecting hydrazine in vitro and in living cells. Abstract : Resorufin (RF) is covalently conjugated to graphene oxide (GO). The covalent bonding of RF‐GO shows much better fluorescence quenching efficiency. RF‐GO can efficiently respond to N2 H4 both in vitro and in living cells.